ANALYSIS OF THE ROLE OF THE WOMEN'S EMPOWERMENT & CHILD PROTECTION OFFICE OF PADANG CITY IN HANDLING CASES OF SEXUAL VIOLENCE AGAINST CHILDREN IN THE FAMILY ENVIRONMENT OF PADANG CITY: ANALISIS PERAN DINAS PEMBERDAYAAN PEREMPUAN & PERLINDUNGAN ANAK KOTA PADANG DALAM MENANGANI KASUS KEKERASAN SEKSUAL TERHADAP ANAK DI LINGKUNGAN KELUARGA KOTA PADANG - Over Nurhasanah; Rizki Syafril (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Sexual violence against children in the family environment is a complex issue influenced by cultural norms, social stigma, and low public awareness in reporting cases. In West Sumatra, especially Padang City, the Minangkabau culture that upholds family honor is one of the main challenges in handling sexual violence. Many victims are reluctant to report due to fear of stigma and social pressure, resulting in suboptimal case handling. In this context, the role of the Women's Empowerment and Child Protection Office (DP3A) of Padang City is very important in protecting victims, providing assistance services, and initiating prevention and public education. This research uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews with DP3A of Padang City, document analysis, and relevant literature studies. To analyze the role of DP3A, four sociological indicators of role according to Rohidi (2013) were used, namely: role as a pattern of expected behavior, as a social obligation, as part of social identity, and as social interaction. The research focuses on how DP3A carries out these roles in handling cases of sexual violence against children in the family environment, as well as the challenges faced in its implementation. The results showed that DP3A of Padang City has actively carried out its role through policy formulation, cross-sector coordination, provision of psychosocial services, and community education. DP3A also facilitates P2TP2A and PATBM units in 104 urban villages to expand protection coverage. However, the main challenges remain social stigma, limited resources, and suboptimal reporting systems and legal protection. Therefore, synergy is needed between government agencies, law enforcement officials, NGOs, and the community in creating a comprehensive protection system that favors victims